Development of FMCW reflectometry in distributed strain measurement - Won, Pei Chin. (2008)
In recent years, there has been a considerable interest in the development of distributed optical fiber strain sensor due to its advantage of being able to measure the magnitude of strain and detect the location of occurrence simultaneously. This special feature, when applied to strain monitoring, is unapproachable if a strain gauge is used.